India’s look North Policy to Connect Central Asia Policy: A Pragmatic Policy of Indian Foreign Policy - Bimalendu Ghosh (UIN Sunan Gunung Djati, 2022)
Look North Policy is the important policy of the India’s foreign policies. It was initiated by P.V. Narasimha Rao government and then it will be continuing by successor governments and it is still ongoing. India’s abroad first air base, Ayni Air base at Tajikistan, becoming the full member of Shanghai Cooperation Organization, becomes the part of Chabahar port in Iran, beginning of Mumbai-Moscow Corridor etc. all are the part of the India’s Look North Policy. India is considered one of the emerging major powers of the world. This emerging is accredited to several indicators, the primary ones being its demographic trends and a rapidly expanding economy and military. But India also needs to continue its growing status and becomes an influential actor on the international stage when compared to the United States, China, United Kingdom, France and Russia. Look North Policy to Connect Central Asia Policy may become helpful tool for India to become a major global power.